Enikő Vincze, Cornel Ban, Sorin Gog a Jon Horgen Friberg (Eds.): The political economy of extreme poverty in eastern Europe. A comparative historical perspective of Romanian Roma: Routledge, 2025, 234 s. ISBN 9781032862545 - Creţan, Remus (Romano džaniben, 2025)
RECENZE KNIHY